The profile and detection of bribery in Norway and England & Wales: a comparative study - Andresen, Sognnæs Mari (European journal of criminology, 2019)
This paper provides the first significant profile of offenders convicted of bribery in England & Wales (E&W) and Norway, based upon a sample of 75 cases from E&W and 46 from Norway, which were collected through searches of the media and other relevant sources between 2003 and 2015. The paper provides a profile of bribe payers and takers: in both E&W and Norway they are predominantly male, middle aged and involved in a median bribe of between £20,000 and £30,000; the sectors experiencing the most bribes paid are public administration and defence and the sector paying the most bribes is construction. In both countries, the period from the start of the crime to conviction was around six years. The paper also notes some significant differences between the two countries. In Norway there was a larger percentage of higher-grade professionals involved in bribery and in E&W detection by law enforcement was more common, suggesting greater interest by such bodies. The average sentence received by offenders was also slightly higher in E&W. The paper offers many other insights into the characteristics of bribery in the two countries in a rarely researched area.